AL-ADAB AL-ISLAMI BAINA AL-QIYAM AL-KHULUQIYAH WA AL-JAWANIB AL-FANNIYAH - Elwaleed Abdulraouf Elminshawi (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2015)
Art is the formal study of moral standard and correct. The term ethics and morality are often used interchangeably indeed. They usually can mean the something, and in casual conversation. There isn't a problem with switching between one and other when discussing morality it is important to distinguish between morals and values. Both are aspects of human conduct and human interaction, but they are very different types of conduct. The objective of the article is to discuss an Islamic writer could comprises between his Islamic obligation on the technical demands of literature work. It discusses how is the literature work, viewed from moral values and the art of Islamic values.DOI: 10.15408/a.v2i2.1942